9: AN IN VIVO MODEL OF HUMAN AIRWAYS FOR INVESTIGATING FIBROSIS. Issue 3 (23rd February 2016) - Ferrante, S; Hackett, T; Hoptay, C; Engelhardt, J; Ingram, J; Zhang, Y; Alcala, S; Shaheen, F; Matz, E; Pillai, D; Freishtat, R
Abstract : Purpose of Study: Limited models exist to investigate the airway epithelium's role in repair, regeneration, and pathology of chronic obstructive lung diseases. We introduce a human asthmatic airway epithelial xenograft system integrating a proliferating and differentiating airway epithelium with an actively remodeling rodent mesenchyme in an immunocompromised murine host. We hypothesized that epithelial regeneration in asthma induces underlying matrix fibrosis. Methods Used: Human airway epithelial cells from asthmatic and non-asthmatic donors (n=5 per group) were seeded into decellularized rat tracheas. Tracheas were ligated to a sterile tubing cassette and implanted subcutaneously in the flanks of athymic nude mice. Grafts were harvested at 2, 4, or 6 weeks for analysis of tissue histology, fibrillar collagen deposition, and TGFβ1 activation. Non-transplantable human lungs from asthmatic and non-asthmatic donor FFPE sections were analyzed using similar methods. Summary of Results: Grafted epithelial cells generated a differentiated epithelium with basal, ciliated, and mucus cells. By 4 weeks post-engraftment, asthmatic-derived epithelia showed decreased numbers of ciliated cells and E-cadherin expression compared to non-asthmatic controls, similar to human lung biopsy tissue. While there was no evidence of matrix remodeling in acellular xenografts, grafts seeded with asthmatic-derived epithelial cells had 3 times as much fibrillar collagen at 6 weeks post-engraftment as non-asthmatic epithelial seeded grafts. This was accompanied by a >2-fold induction of matrix TGFβ1 [with evidence of pSMAD3 activity] in asthmatic grafts at 4 weeks (positive pixels/total field pixels=0.12±0.001 vs. 0.05±0.001; p=0.003) and 6 weeks (0.09±0.02 vs. 0.04±0.01; p=0.044) post-engraftment. Conclusions: We show in this model that asthmatic epithelium alone is sufficient to drive aberrant mesenchymal remodeling, specifically with fibrillar collagen deposition in asthmatic-derived xenografts.These xenografts are a major advance over current animal models of asthma in that they permit direct assessment of the epithelial-mesenchymal trophic unit.